ESPOROTRICOSE FELINA: RELATO DE CASO - Schneider, Esther Pischke; Hans, Sandra De Bona; Moura, Merlin; Festugatto, Rafael; Pinheiro, Fernanda; Lusa, Tatiane; Wurfel, Simone de Fátima Rauber (Anais de Medicina Veterinária, 2022)
.